Dynamic DNA methylation changes in early versus late adulthood suggest nondeterministic effects of childhood adversity: a meta-analysis. (14th October 2021) - Artigas, Rocio; Vega-Tapia, Fabián; Hamilton, James; Krause, Bernardo J.
Abstract: Adverse childhood experiences (ACEs) are associated with a high risk of developing chronic diseases and decreased life expectancy, but no ACE epigenetic biomarkers have been identified until now. The latter may result from the interaction of multiple factors such as age, sex, degree of adversity, and lack of transcriptional effects of DNA methylation changes. We hypothesize that DNA methylation changes are related to childhood adversity levels and current age, and these markers evolve as aging proceeds. Two Gene Expression Omnibus datasets, regarding ACE, were selected (GSE72680 and GSE70603), considering raw- and meta-data availability, including validated ACE index (Childhood Trauma Questionnaire (CTQ) score). For DNA methylation, analyzed probes were restricted to those laying within promoters and first exons, and samples were grouped by CTQ scores terciles, to compare highly (ACE) with non-abused (control) cases. Comparison of control and ACE methylome profile did not retrieve differentially methylated CpG sites (DMCs) after correcting by false discovery rate < 0.05, and this was also observed when samples were separated by sex. In contrast, grouping by decade age ranges (i.e., the 20s, 30s, 40s, and 50s) showed a progressive increase in the number of DMCs and the intensity of changes, mainly related with hypomethylation. Comparison with transcriptome data for ACE subjects in the 40s, and 50s showed a similar age-dependent effect. This study provides evidence that epigenetic markers of ACE are age-dependent, but not defined in the long term. These differences among early, middle, and late adulthood epigenomic profiles suggest a window for interventions aimed to prevent the detrimental effects of ACE.